THE CONCEPTUAL BASIS OF STUDENTS’ SUBJECTIVITIES TO THE PROFESSIONAL AND PEDAGOGICAL FUTURE PERFORMANCE - Shekhavtsova, Svitlana (Journal of Education Culture and Society, 2020)
We discussed the notion of “students’ subjectivities” from the current psychological and pedagogical point of view. The author investigates the notion in its historical development. The paper reviews the developing students’ subjectivities, focusing on students’ abilities and personal characteristics, such as students’ setting goals, achievement values, recognizing actual or potential perspectives. The article aims to study the problem of developing students’ subjectivities and to carry out theoretical analysis of students’ subjectivities showing the historical development of this category and reflecting the stages of students’ professional and pedagogical development. The target group of students are students related to pedagogical teaching practice. Relations between students’ subjectivities and the efficiency of their future professional and pedagogical performance are discussed, as well as how to develop students’ subjectivities creating special pedagogical conditions during the academic process in the university. We also focus on stages of students’ professional and pedagogical development, such as the stage of students’ professional training, professional adaptation stage and directly professionalization. In this regard, we present the core conceptual bases of students’ subjectivities development to professional and pedagogical performance. The conceptual bases highlight the idea of ​​students’ gradual change from one stage of students’ professional and pedagogical development to the following ones; the idea of the organization of reflective teaching activities of students’ interaction in the development of students’ subjectivities; and the idea of ​​interpreting the mechanisms of the students’ subjectivities development.